Die Anfänge der Gegenwart. Umbrüche in Westeuropa nach dem Boom - Schlemmer, Thomas (Zeitgeschichte im Gespräch, 2014)
Contemporary observers were already aware that the 1970s and 1980s were a time of accelerated change. There were simultaneous breakthroughs in many areas, which permanently transformed politics, society, and culture. People were quick to note that these post-boom years were a turning point. This volume traces the upheavals of the 1970s and 1980s by looking at selected examples to sharpen our awareness of the origins of the present.